Prevalence of the sick building syndrome symptoms in office workers before and after being exposed to a building with an improved ventilation system. - Bourbeau, J (1996)
OBJECTIVE: To find if the prevalence of symptoms associated with sick building syndrome decreased among office workers after moving to a building with improved ventilation (after controlling for potential confounders). METHODS: Workers in five buildings in 1991 all moved in 1992 into a single building with improved design, operation, and maintenance of the ventilation system. All buildings had sealed windows with mechanical ventilation, air conditioning, and humidification. Workers completed a self administered questionnaire during normal working hours in February 1991 and February 1992. The questionnaire encompassed symptoms of the eyes, nose and throat, respiratory system, skin, fatigue, headache, and difficulty concentrating, personal, psychosocial, and work related factors. During normal office hours of the same week environmental variables were measured. RESULTS: The study population comprised 1390 workers in 1991 and 1371 workers in 1992 who represented more than 80% of the eligible population. The prevalence of most symptoms decreased when workers moved to the new building: skin (54%), respiratory system (53%), nose and throat (46%), fatigue (44%), headache (37%), eyes (23%). These findings were all significant and remained generally similar after controlling for personal, psychosocial, and work related factors. Furthermore, more than 60% of workers symptomatic in 1991 were asymptomatic in 1992 for all types of symptoms. In contrast, less than 15% of workers were asymptomatic in 1991 but symptomatic in 1992 for all types of symptoms. CONCLUSION: In this study, the prevalence of most symptoms usually associated with the sick building syndrome decreased by 40% to 50% after workers were transferred to a building with an improved ventilation system. The results show that it is possible to diminish the prevalence of symptoms associated with the sick building syndrome among office workers occupying a building with mechanical ventilation, air conditioning, and sealed windows.